An Analysis of Students' Problems of Speaking English in Grade VIII of SMPN 3 Sungai Limau - Yolla Syahdila; Edi Trisno (Journal of English Language Teaching, 2023)
This study aims to know the students’ problems of speaking English and the dominant problems faced by students at grade eight of SMPN 3 Sungai Limau. The design of this research is descriptive research. The data were collected by using questionnaire and interviews. In this research, the researcher used total sample as a sampling technique for choosing the participants. The participants of this research consist of 79 students at grade eight from class VIII.1, VIII.2, and VIII.3 of SMPN 3 Sungai Limau. The result of this research find that the students have problems in linguistics problems and psychological problems. The linguistics problems consist of incorrect pronunciation with a percentage 88.61%, and followed by lack of vocabulary with, and mastering of grammar with same percentage 81.33%. The psychological linguistics consist of anxiety with a percentage 68.67%, mother tongue use with a percentage 72.15%, shyness with a percentage 70.25%, lack of confidence with a percentage 73.42%, and fear mistakes with a percentage 73.73%. The dominant problems face by the students in speaking English is linguistics problems with average 73.51%.